TRANSFORMASI BUDAYA ORGANISASI DI VIZ CAKE PEKANBARU - Handika, Yudi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The study aims to determine how the transformation of organizational culture in Viz cake Pekanbaru. The study with kualitatif. Approach the study positivism. Techniques of collecting data through interviews. Informants as much as 5 people. Based on the interviews, process of transformation in Viz cake Pekanbaru at 2012. And in process of transformation as well. Transformation occur caused.of Viz cake Pekanbaru leader’s change old value not approriate with corporate and environment to be adaptif and be able accept with well by employees.Keywords : Organizational culture, transformation of culture